History of Rakhine State and the Origin of the Rohingya Muslims - Haradhan Kumar Mohajan (Center for Southeast Asian Social Studies (CESASS), 2018)
The Rohingya, a Muslim ethnic minority group in Rakhine, are considered among the most persecuted, vulnerable, and oppressed minorities in the world. Recently, the persecution on the Rohingya Muslims has increased due to Buddhist nationalism in Myanmar. The Rohingya continue to suffer from several forms of restrictions and human rights violations in Myanmar due to them being denied Myanmar citizenship. They are victims of various forms of oppression, such as arbitrary taxation, land confiscation, destruction of mosques, torture and ill-treatment, extrajudicial executions, restrictions on movements, forced eviction and house destruction, forced laborers on roads and at military camps, and financial restrictions on marriage. Since the 1970s, a number of crackdowns on the Rohingya in Rakhine have forced them to flee to neighboring countries. More than one million Rohingyas have migrated to refugee camps in the Bangladeshi district of Cox’s Bazar. This article deals with the origin of the Rohingya, the form of their citizenship, and recent oppression in the Rakhine State of Myanmar.